How can we improve the diagnosis of heart failure?. Issue 12 (December 2022) - Thomson, Clare; Cuthbert, Joe; O'Nwere-Tan, Teresa Adaora
Prevention and management of cardiovascular disease is a key priority for the National Health Service (NHS); it is central to the NHS England Long Term Plan, and from April 2022 it also forms a large proportion of the Direct Enhanced Service Contract for all primary care networks. Diagnosis and management of hypertension, hypercholesterolaemia and atrial fibrillation are routine in primary care but, despite increasing prevalence, heart failure is arguably falling behind. Heart failure can be challenging to diagnose and there may be few initial symptoms when patients first present. However, patient quality of life and life expectancy dramatically improve with an early diagnosis and prompt initiation of treatment. This article provides a framework for initial diagnosis and management in primary care.